Contact [videorecording (DVD)] - Zemeckis, Robert, 1952-; Foster, Jodie; McConaughey, Matthew, 1969-; Woods, James, 1947-; Sagan, Carl, 1934-1996 (Warner Home Video, 1997)
Astronomer Dr. Ellie Arroway receives an encrypted message, apparently from a solar system many light-years away.